PENGARUH PEMBERIAN INSENTIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT INDOMARCO PRISMATAMA AREA CABANG JAKARTA 1 - Annisa; Hamdi Supriadi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of providing incentives and work discipline on employee performance at PT Indomarco Prismatama Jakarta branch area 1. This study was conducted using a quantitative research method with a sampling technique using saturated sampling and samples were obtained in the study of 65 respondents. Data analysis uses validity test, reliability test, classical assumption test regression analysis, determination coefficient analysis and hypothesis test. The result of thus are that provision of incentives has a significant effect on employee performance with the regression equation Y = 21.183 + 0.440 X1, a correlation value of 0.571 meaning that the two variables have a moderate level of relationship. The value of determination coefficient was 32.6%. The hypothesis test was obtained by calculating t > t table or (5.522 > 1.669) thus H0 is rejected and H1 is accepted meaning that there is a significant influence of providing incentivies on employee performance. Work discipline has a significant effect on employee performance with the regression equation Y= 17.539 + 0.523 X2 correlation value 0.630 meaning that the two variables have a strong relationship level. The value of the determination coefficient is 39.7%. the hypothesis test was obtained by t counting > t table or (6.437 > 1.669). thus, H0 is rejected and H2 is accepted meaning that there is a significant influence of work discipline on employee performance. The provision of incentives and work discipline had a significant effect on employee performance with the regression equation Y = 13.378 + 0.255 X1 + 0.378 X2 correlation value 0.690 meaning that the independt variable with the bound variable had a strong relationship level. The coefficient value of determination was 47.6% while the remaining 52.4% was influenced by other factors.